Oracular messages in Greek novels: religious element or narrative device? (Argos, 2026)
This article compares the use of oracular messages in different Greek novels: An Ephesian Tale by Xenophon of Ephesus (1st century), An Aethiopian Story by Heliodorus (3rd-4th centuries) and Rhodante and Dosikles by Theodore Prodromos (12th century). A tension emerges between the narrative necessity of introducing an oracle to advance the plot and the interests of certain characters or narrators, which at times conflict with narrative functionality. Comparing the selected scenes raises the question of whether the oracle is incorporated as a religious element or as just another literary topos.
Keywords: Greek novel; Oracle; Religion; Fiction